Towards electronic government focused on administrative procedure automation - Wojciechowski, Rafał; Strykowski, Sergiusz (W stronę elektronicznej administracji ukierunkowanej na automatyzację postępowań administracyjnych, 2012)
E-government is implemented mainly through the deployment of IT solutions improving the selected functional aspects of public administration units, but not improving the functioning of public administration as a whole. To achieve a significant synergy effect in relation to the benefits for citizens and businesses, we propose an e-government framework focused on administrative procedure automation. The proposed framework is based on three pillars: e-government services, automated administrative procedure execution and public register services. The pillars are founded on electronic documents. The key objective of the framework is to automate the execution of administrative procedures as it significantly increases public administration efficiency and thus brings the greatest benefits for citizens and businesses
Informatyka Ekonomiczna = Business Informatics, 2012, Nr 2 (24), s. 104-114
Keywords: e-government; administrative procedure; automation; electronic service; electronic document; public register; elektroniczna administracja; postępowanie administracyjne; rejestr publiczny